Corporate governance mechanisms and intellectual capital disclosure in Malaysian GLCs / Hartini Azman - Azman, Hartini (2011)
The objective of this study is primarily to investigate the influence of corporate governance as well as controlling for corporate characteristics like company size on IC disclosure for a sample of Malaysian GLCs that is listed in Kuala Lumpur Composite Index (KLCI). In this study annual report from 78 Malaysian GLCs listed in the KLCI will be used for source of information in order to analyze the IC disclosure on 2007 till 2009. The IC disclosure as dependent variable consists of relational capital, structural capital and human capital are measured by using disclosure index score. Corporate governance mechanisms as independent variables cover of ownership structure (share concentration), board of directors (Independent non executive directors (INED) and cross directorship) and board of committee (audit committee size and meeting). Results indicate significant of all corporate governance mechanisms except INED and audit committee size together with company size in term of total asset are related with one or more of the IC disclosure types. Thus, it give details explanation wherein share concentration show significant as companies that holding more on share concentration will be less reported on IC items as dominant shareholders can be easily to access the information they needed and give them less pressure to disclose IC in annual report. Cross directorship indicate to be significant positive relationship with IC disclosure because cross directorship hold by the member of boards lead to a positive implications for disclosure practice since they are able to get a greater and better access of information more than one company as well as to abolish any secrecy information as encouraging voluntary disclosure indirectly. While, audit committee meeting shows significant positive relationship with IC disclosure as by having more meeting between audit committee may also encourage to provide more IC disclosure in annual report and company size in term of total sales also has significant positive relationship as big companies are more visible and expected to meet investors demand for information compared with small companies. It is due to the more revenue generated by big companies which shows that the company is good enough capacity of assets to bring benefit to the company (Li et al, 2008). Besides, bigger companies may have more involvement of stakeholders who is interested to know on how company manages IC.